IS THE APPLAUSE SIGN USEFUL FOR DIAGNOSIS OF DEMENTIA AND MCI?. Issue 11 (14th October 2015) - Bonello, Michael; Larner, Andrew
Abstract : Objective: To examine the diagnostic utility of the applause sign for dementia and MCI in consecutive referrals to cognitive disorders clinic. Results: Over a 10–month period (January–November 2014) 243 consecutive new outpatients (F:M=124:119; age range 18–91 years, median 61) were administered the applause test ("clap 3 times"). Of the 240 with interpretable results, 46 were diagnosed with dementia (DSM–IV criteria), 66 with MCI (Petersen criteria), and 128 with no cognitive impairment. Using the categorization of applause sign from Luzzi et al. (2011), the percentage of patients with any cognitive impairment who clapped 3–10, and >10 times was 38.9, 60, 70.8, and 87.5 respectively. The null hypothesis that the proportion of patients with cognitive impairment did not differ significantly between groups was rejected (χ2=21.4, df=3, p<0.001). Abnormal scores (>3 claps) had sensitivities for dementia, MCI, and any cognitive impairment of 0.52, 0.24, and 0.36 respectively, and specificities of 0.84, 0.88, and 0.88. Conclusions: This pragmatic study confirms and extends the results of a previous smaller study (n=100) of applause sign in the cognitive clinic, showing the applause sign to be a high specificity low sensitivity test for cognitive impairment.